Assessing the effect of energy poverty on the mental and physical health in China—Evidence from China family panel studies - Xu, Wangzi; Xie, Baiwei; Lou, Bailu; Wang, Weizheng; Wang, Yuzi (Frontiers in Energy Research, 2022)
Energy poverty is a crucial issue faced by countries all around the world, as the largest developing country in the world, China is also experiencing energy poverty problems. In order to explore the health effect of energy poverty in China, this paper first uses the principal component analysis (PCA) to construct a comprehensive index to measure energy poverty, and then adopts the ordinary least square method (OLS), fixed effect model (FE), instrumental variable two-stage least squares (IV-2SLS) regression to study the impact of energy poverty on the physical and mental health of Chinese people based on China Family Panel Studies 2018 (CFPS 2018). The study discovers that energy poverty significantly hampers the mental and physical health of Chinese people, an increase in energy poverty might cause 28.74%、18.69% decrease in mental and physical health respectively. Moreover, this paper further explores the influencing paths of energy poverty by intermediary effect and regulatory effect. It is revealed that in addition to directly affecting physical and mental health, energy poverty also have a negative impact on physical and mental health by affecting the accessibility of a series of resources, such as water and food, reducing the opportunities for physical exercise and increasing medical expenses. However, the impact is restricted by age and family income. Finally, under the national strategy of China, this paper further discusses how to give consideration to the joint implementation of heath and emission reduction strategies, then gives specific policy suggestions based on the results.